Integrating user requirements and ergonomics in designing a school workshop workstation / Adila Md Hashim - Adila, Md Hashim (2013)
Many studies showed that schoolchildren and adolescent faced risk of musculoskeletal disorder due to furniture mismatch in school. However, very few studies evaluate the extend of a possible mismatch between school workshop furniture to schoolchildren’s body postures. It may be due to variety of furniture design in school workshop. Furniture mismatch and inappropriate workstation design may contribute to early symptoms of muskuloskeletal disorder and back pain among schoolchildren. The purpose of this study was to evaluate students’ working postures when using the school workshop’s workstation and recommended an ergonomically workstation design for future school workshop furniture guidelines. This study was carried out at a suburb secondary school in Klang district of Selangor, Malaysia. A total of 320 students aged 13 to 15 years old participated for questionnaire survey. 6 students were randomly selected for physical posture evaluation when using the current workstation. Each student was represented for each age and gender. 260 and 205 students were selected for Kano model and User importance survey respectively to discover user requirement. 145 students participated in anthropometry data measurement using manual and 3 dimension body scanning methods for a new designed workstation. Finally, the Jack simulation software was used to evaluate students’ working postures when interact with the proposed workstation. Results showed that short students faced higher risks of developing musculoskeletal disorder when using the current workstation regardless the age and gender. Short students has higher scores in physical assessment methods. Kano model and Quality Function Deployment integration analysis indicated that safety application and broad working surface were important requirements for the students. In addition, technical requirement result suggested that design stardard and comfort element were the important features for the proposed design. Finally, the simulation analysis indicated that shorter students have reduced the scores in RULA method significantly. The risk level also changed to lower level when using the proposed workstation. In conclusion, this study provides some significant insights on the need of workstations evaluation for technical and vocational classroom of secondary schools in Malaysia.